(untitled) (Journal of the College of Basic Education, 2024)
Handball is a team sport that requires its players to have special physical and skill abilities and to perform with high efficiency throughout the match. Building training curricula lacks a connection between modern training methods that are in line with the developments taking place in the game of handball, and the researcher’s attempt to break out of the stereotypes followed in The traditional training curriculum and creating variable responses to bring about development in the offensive skills of handball players. The goal of the research is to prepare a training curriculum in the style of CrossFit training, to identify the effect of the training curriculum on some anthropometric measurements and offensive skills in handball, The researcher used the experimental method by designing the experimental and control groups with a pre- and post-test. The research population was chosen intentionally from the players of Al-Nasr Club in Dhi Qar, the youth category, who numbered (20 players), and after excluding the goalkeepers (2), thus the sample became (18 players). Continue In training, the research sample was divided randomly by lottery into two groups, experimental and control, with (9) players for each group. The implementation of the training program began for a period of (12) weeks, with (3) training units per week, and the total number of units was (36), and the researcher concluded that The CrossFit exercises prepared by the researcher had an effective impact in developing physical measurements, which had a clear impact that was reflected in developing the performance and offensive skills of the research sample.